2019
DOI: 10.5144/0256-4947.2019.444
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five year-old female with sudden onset itchy skin eruption over her upper back and chest three weeks after starting a ketogenic diet

Abstract: Prurigo pigmentosa is a rare pruritic inflammatory dermatosis with a unique staged clinicopathological presentation. It was first reported by Nagashima in 1971, and recently, more cases have been reported We introduce a case of a young Saudi female who developed biopsy proved prurigo pigmentosa after she followed strict ketogenic diet. Her condition resolved after she resumed a regular diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In a case series of nine patients, Goh et al 11 found that 33.3% of their cases were on KD before PP appearance. Furthermore, several other cases have reported the induction of PP following KD commencement with a satisfactory improvement of the lesions following the reintroduction of carbohydrates 7,11–23 . In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients.…”
Section: Ref No Age/gender Duration Of Diet Before Pp Onset (Day) Tre...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of nine patients, Goh et al 11 found that 33.3% of their cases were on KD before PP appearance. Furthermore, several other cases have reported the induction of PP following KD commencement with a satisfactory improvement of the lesions following the reintroduction of carbohydrates 7,11–23 . In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients.…”
Section: Ref No Age/gender Duration Of Diet Before Pp Onset (Day) Tre...mentioning
confidence: 99%
“…International Journal of Dermatology 2022, 61, 779-782 reintroduction of carbohydrates. 7,[11][12][13][14][15][16][17][18][19][20][21][22][23] In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients. Most of the patients were female (18/22; 81.8%) with an average age of 24.9 years old.…”
mentioning
confidence: 99%